2009
DOI: 10.2459/jcm.0b013e32832d495e
|View full text |Cite
|
Sign up to set email alerts
|

Heartmate II axial-flow left ventricular assist system: management, clinical review and personal experience

Abstract: Long-term HeartMate II LVAD provides good mid-term, long-term results. This new technology requires delicate management. Functional status and quality of life greatly improve in patients who survive the perioperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 18 publications
0
21
1
Order By: Relevance
“…Because axial CF pumps typically do not derive accurate pump flow values and do not have the degree of pump flow pulsatility of centrifugal CF pumps, they tend to rely on detection of a suction event after it occurs based on the sensed disturbed flow and motor current feedback when intermittent inlet cannula suction takes place. [22][23] The HeartMate II system does automatically decrease pump speed in response to a suction event. Hertzer et al 24 have reported that the INCOR axial flow pump has an automatic anti-suction algorithm based on flow pulsatility falling below a pre-determined minimum level, and recent publications indicate that Berlin Heart Inc, is developing and testing algorithms for automatic pre-load-sensitive control of rotary blood pumps.…”
Section: Suction-detection Algorithmsmentioning
confidence: 99%
“…Because axial CF pumps typically do not derive accurate pump flow values and do not have the degree of pump flow pulsatility of centrifugal CF pumps, they tend to rely on detection of a suction event after it occurs based on the sensed disturbed flow and motor current feedback when intermittent inlet cannula suction takes place. [22][23] The HeartMate II system does automatically decrease pump speed in response to a suction event. Hertzer et al 24 have reported that the INCOR axial flow pump has an automatic anti-suction algorithm based on flow pulsatility falling below a pre-determined minimum level, and recent publications indicate that Berlin Heart Inc, is developing and testing algorithms for automatic pre-load-sensitive control of rotary blood pumps.…”
Section: Suction-detection Algorithmsmentioning
confidence: 99%
“…They are widely used in the axial blood pumps, with reduced risk of blood clot formation in the low flow area a bearing, due to positioning of the bearing in the main blood flow path [9]. Utilization of mechanical bearings in the centrifugal blood pumps can lead to clot formation between the impeller and the pump case, as a consequence of flow speed reduction and the increased time of blood cells residence in the bearing area.…”
Section: Discussionmentioning
confidence: 99%
“…In many cases this can be easily corrected by assuring adequate volume status, but many patients require cardiac pacemakers or implantable cardioverter defibrillators (ICDs) to help control malignant ventricular dysrhythmias. 2,7 The additional implantation of an ICD increases the risk of complications. 2 Monitoring and control of BP in patients with continuous-flow LVADs can be challenging.…”
Section: Join Our Team Today For a World Of Opportunities And An Excimentioning
confidence: 99%
“…6 Because of their low weight and small size, continuous-flow LVADs can be implanted in a wide variety of patients, including women and smaller adults. 7 Generally, these devices are surgically implanted below the left rib cage in a preperitoneal position (see Looking at an LVAD). The inflow cannula delivers blood from the ventricle into the pump, and the outflow cannula carries blood from the pump to the ascending aorta.…”
Section: Smaller Is Bettermentioning
confidence: 99%
See 1 more Smart Citation